Analysis of Collaborative Actors in Regional Inflation Control Using Social Network Analysis - Anindita Primastuti; Sartika Ika; Muhadam Labolo; Bahrullah Akbar (Institut Pemerintahan Dalam Negeri, 2023)
This study aimed to analyze the relationships among actors involved in the collaboration of the Regional Inflation Control Team (TPID) in Cilacap Regency and identify the main actors (key actors) who play a crucial role in its success. Social Network Analysis was used to examine the network among the actors focus on four factors namely; collaboration, communication, learning examples, and interactor relationships within TPID. The results showed that the following actors were considered important in the TPID collaboration for inflation control in Cilacap Regency, namely theRegent of Cilacap, the Secretary of Cilacap Regency, the Head of the Bank Indonesia Representative Office in Purwokerto, the Assistant for Economic and Development, as well as the Head of Trade, Economy, and SMEs Office. These individuals were often sought after and served as learning resources when TPID members encountered problems. Keywords: Inflation; Collaborative Public Management; Collaboration; Communication; Social Network